Le lettere di Lodovico Castelvetro. Con una lettera inedita di Agostino Gadaldini (Quaderni di Gargnano, 2018)
The paper comments on the critical edition of the letters of Lodovico Castelvetro (1505-1571) published in 2015 (Rome, Edizioni di Storia e Letteratura — Bites Edizioni: http://bitesonline.it/lettere-rime-carmina/). The surviving letters of Lodovico Castelvetro, a famous critic and philologist, are mostly addressed to local correspondents and deal mainly with contemporary news and erudite subjects. Some of the letters develop into short essays on topics such as the principles of translation or questions of etymology. The second part of the paper examines the methodology used to compile the critical edition of the letters. The appendix includes a critical edition of a previously unpublished letter written by Agostino Gadaldini to Castelvetro (Venice, 27th October 1553).
Keywords: Lodovico Castelvetro; Agostino Gadaldini; Critical edition; Epistolarity